PERFORMANCE EVALUATION OF EDUCATIONAL INSTITUTIONS IN IRAQ USING INTEGRATING (DEA- EWM-WSM) APPROACH - Abbas Awaid Abd Al hussein; Rasheed Al-Salih (Scholar Express Journals, 2023)
This study focuses on assessing the performance of educational institutions in Iraq using new efficient technique. The presented approach consists of three stages: first, (DEA) is employed to identify efficient and inefficient decisionmaking units, in the second stage, the entropy weights method (EWM) is applied to determine the relative importance of the input and output of the decision-making units, and in the third stage, weighted sum model (WSM) is used to rank the efficient decision making units. Also, the study suggest that inefficient units can improve their efficiencies by learning from the strategic that adopted by these efficient decision making units.
Keywords: Performance Evaluation; educational institutions